A Superhydrophobic Surface Templated by Protein Self-Assembly and Emerging Application toward Protein Crystallization - Gao, Aiting (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.